Development of non-destructive vibration method for classification of bone fracture severity - JANI, Jignesh; RACHCHH, Nikunj (Applied Computer Science, 2026)
Accurate classification of bone fracture severity is critical in orthopedic evaluation. Radiation-based methods such as X-ray, CT, and MRI provide anatomical detail but lack the ability to classify fracture severity. This study presents a non-invasive, vibration-based approach to assessing fracture severity by analyzing dynamic response characteristics. Five goat (metacarpal) bone specimens were examined, including one unfractured bone that served as a reference bone and four with induced fractures in the lateral, longitudinal, and two oblique orientations. Controlled impact excitation was applied using an impact hammer, and acceleration responses were measured using acceleration sensors. Frequency response function (FRF), coherence, and phase shift were calculated using Fast Fourier Transform (FFT) algorithms. Resonance frequency and FRF magnitude served as primary indicators of stiffness loss and damping changes caused by fractures. The reference bone had a resonance frequency of 376 Hz and an FRF magnitude of 12.96 g/N, which was considered the reference parameter. The lateral fracture showed the most severe response, with a 17.98% increase in resonant frequency and a 491% increase in FRF magnitude, indicating significant stiffness redistribution and low damping. Longitudinal and oblique fractures resulted in large resonant frequency reductions of up to 94.4%. The experimental results were obtained using Fast Fourier Transform (FFT) algorithms and Euler-Bernoulli ray theory. These results suggest that vibration analysis is a reliable, quantitative, and non-destructive tool for classifying the severity of bone fractures.